Astronomy Study: Determination of the Beginning of the Hijriyah Month Perspective of the Interpretation of the Ministry of Religion of the Republic of Indonesia and LIPI - Muhammad Yuchbibun Nury; Dhur Anni; Slamet Arif; Mariyatul Qibtiyah (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
The difference between the determination of the beginning of the month is a problem that until now can lead to disputes in the community. Especially the differences between Islamic mass organizations in Indonesia. The formulation of the problem in this study are; 1) What is the interpretation of the hilal verses from the perspective of the Ministry of Religion and LIPI's interpretation? 2) How is the implementation of the interpretation of the hilal verses by the Ministry of Religion in determining the beginning of the Hijriyah month?. This research is in the form of library research using the method of presenting descriptive and analytical data. The determination of the beginning of the lunar month in the interpretation of the Ministry of Religion of the Republic of Indonesia and LIPI provides an understanding that the moon provides several benefits for the inhabitants of the earth as its mother planet. RI Ministry of Religion and LIPI share the benefits of the moon for human life on earth for 3 things; 1) Moon as a satellite of the earth, 2) Moon as a tidal mover, 3) Moon as a time maker.